Advanced Methods of Continuum Mechanics for Materials and Structures - Naumenko, Konstantin; Aßmus, Marcus; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume presents a collection of contributions on advanced approaches of continuum mechanics, which were written to celebrate the 60th birthday of Prof. Holm Altenbach. The contributions are on topics related to the theoretical foundations for the analysis of rods, shells and three-dimensional solids, formulation of constitutive models for advanced materials, as well as development of new approaches to the modeling of damage and fractures.
Part I: Fundamentals and Elasticity -- 1 Time derivatives in material and spatial description - What are the diﬀerences and why do they concern us? -- 2 The Cosserats' memoir of 1896 on elasticity -- 3 On equivalent inhomogeneities for particles with multiple-component interphases -- The inﬂuence of distributed dislocations on large deformations of an elastic sphere -- 4 Part II: Visco-Elastic Media and Coupled Phenomena -- 5 A closed-form solution for a linear visco-elastic self-graviting sphere.
Keywords: Mechanics, Applied; Solids; Mathematics -- Data processing; Materials -- Analysis; Building materials; Solid Mechanics; Computational Science and Engineering; Characterization and Analytical Technique; Structural Materials